Effect of leaf thinning on shoot growth and tuber yield of white Guinea yam - Iseki, K.; Olaleye, O.; Matsumoto, R. (Informa UK Limited, 2022)
Mutual leaf shading can inhibit the growth of yam, reducing tuber yield. To improve light utilization, approximately 25% of leaves in a plant were thinned during the period of maximum shoot growth. Shoot dry weight was estimated every two weeks using a non-destructive method. Leaf thinning caused higher shoot growth rates (SGRs) after thinning, while control plants had SGRs close to zero. The higher SGRs in the thinned plants was attributed to an increase in new leaf development. This indicates that the plateau in shoot growth commonly observed during the late growth period is reversible and could be improved artificially. In thinned plants, there was a positive relationship between shoot dry weight and SGR, although no such relationship was observed in control plants after the middle growth period. This positive correlation indicates a higher shoot growth per unit leaf area in the thinned plants than in the control plants, presumably due to improved light utilization and a higher photosynthetic rate of new leaves. However, leaf thinning reduced tuber yields, presumably because of a lower total carbon assimilation per plant and greater growth competition between shoots and tubers. High correlations between shoot dry weight and tuber yield indicated that a high shoot biomass is more important than improving light utilization for increased tuber yields.